2022
DOI: 10.30867/gikes.v3i1.767
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Health Belief Model terhadap pelaksanaan vaksinasi untuk penanggulangan pandemi Corona Virus Diseases-19 (Covid-19) pada tenaga kesehatan Kabupaten Nagan Raya

Abstract: Background: World Health Organization (WHO) has declared Coronavirus Disease 2019 (COVID-19) as a pandemic. Interventions are needed not only in terms of implementing health protocols but also other effective interventions to decrease the transmission of disease through vaccination efforts which are aimed at reducing transmission/transmission of COVID-19, reducing morbidity and mortality due to COVID-19, and achieving group immunity in the community society (herd immunity).Objective: The purpose of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results showed that there was a relationship between cues to act and acceptance of the Covid-19 vaccine in the community in the working area of the Puuwatu Health Center, with a p-value (0.000). This research is in line with research conducted by (Hardiansyah et al, 2021) the results found in this study are that there is a relationship between the signal to act high on the implementation of vaccinations in the context of tackling the Covid-19 pandemic in health workers within the scope of the Nagan Raya District Health Office in 2021 Health workers who have low cues to action have 4.33 times the chance of being given the vaccine (Hardiansyah et al, 2022).…”
Section: Relationship Of Cues To Action With Acceptance Of Covid-19 V...supporting
confidence: 91%
“…The results showed that there was a relationship between cues to act and acceptance of the Covid-19 vaccine in the community in the working area of the Puuwatu Health Center, with a p-value (0.000). This research is in line with research conducted by (Hardiansyah et al, 2021) the results found in this study are that there is a relationship between the signal to act high on the implementation of vaccinations in the context of tackling the Covid-19 pandemic in health workers within the scope of the Nagan Raya District Health Office in 2021 Health workers who have low cues to action have 4.33 times the chance of being given the vaccine (Hardiansyah et al, 2022).…”
Section: Relationship Of Cues To Action With Acceptance Of Covid-19 V...supporting
confidence: 91%
“…According to the Ministry of Health in (Hakim and Bangun, 2021) stated that Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans (Akseer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the COVID-19 vaccination targeting the community is expected to be the desire of all the general public, especially men and women over the age of 18 with healthy conditions to participate in the implementation of the vaccination, considering the awareness of the needs and benefits of the COVID-19 vaccine, so that researchers are interested in conducting a systematic review and meta-analysis of research results that aim to measure the success of implementing the Health Belief Model on the implementation of vaccinations in the context of overcoming the Corona Virus Diseases-19 (COVID-19) pandemic in the general public (Hakim and Bangun., 2021).…”
Section: Introductionmentioning
confidence: 99%